Analisis Beberapa Faktor yang Berhubungan dengan Penggunaan Jamban Keluarga di Desa Ranah Singkuang Kabupaten Kampar - Trismon, Ignatius; Saam, Zulfan; Nazriati, Elda (Universitas Riau, 2016)
People in the village Ranah Singkuang who do not have family toilets still use the land, shrubs and streams to defecate, it was incompatible with the rules of health, so that they can transmit diseases and health problems. This study aimed to analyze the relationship between education, knowledge, attitudes, conditions of latrines and the role of extension with the participation of the community in the use of family latrines in the village of Ranah Singkuang Kampar by using Analytic Survey method with cross sectional design. Research conducted on 64 samples of defined population of 149 people in the village of Ranah Singkuang Kampar district in Riau province. Research shows that education, knowledge and attitudes as predisposing factors have the meaningful relationships with community participation in the use of household toilets, attitude is the most influential factor in which a good attitude will affect eight times participated both in the use of household toilets. As well as enabling factors (conditions of latrines) and reinforcing factors (the role of extension workers) also has a significant relationship with public participation in usage of toilet in the Ranah Singkuang village . Adverse effects as a result of low participation in the use of household toilets are contaminate soil, water and aesthetics, giving rise to the spread of disease to society.